2012
DOI: 10.1093/aob/mcs015
|View full text |Cite
|
Sign up to set email alerts
|

The response of forest plant regeneration to temperature variation along a latitudinal gradient

Abstract: Decreasing seedling emergence and growth were found from the centre to the northern edge of the distribution range for both species. Stronger responses to temperature variation in seedling growth of the grass M. effusum in the north may offer a way to cope with environmental change. The results further suggest that climate warming might differentially affect seedling establishment of understorey plants across their distribution range and thus alter future understorey plant dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 45 publications
6
31
0
Order By: Relevance
“…2); results that are in agreement with some previous studies (De Frenne et al, 2012;Richter et al, 2012). However, in the southwest of Western Australia, Cochrane et al (2015) found that emergence of seedlings was delayed with warmer conditions, compared to control.…”
Section: Factorsupporting
confidence: 91%
“…2); results that are in agreement with some previous studies (De Frenne et al, 2012;Richter et al, 2012). However, in the southwest of Western Australia, Cochrane et al (2015) found that emergence of seedlings was delayed with warmer conditions, compared to control.…”
Section: Factorsupporting
confidence: 91%
“…We have found few reports of reductions and delays in seedling emergence with increasing soil temperatures (though see Chidumayo ). In contrast, soil warming has been reported to lead to earlier seedling emergence in Pinus sylvestris (Richter et al ) and increased emergence in European understorey shrubs (De Frenne et al ). In temperate grasslands, a reduction in seedling emergence with warming was almost solely explained by a decrease in soil moisture potential (Hovenden et al , Gao et al ).…”
Section: Discussionmentioning
confidence: 98%
“…These types of garden effects are a frequent occurrence in studies involving multiple common gardens (e.g., De Frenne et al. , Woods et al. , Zhou et al.…”
Section: Discussionmentioning
confidence: 99%